Darul Aman Furniture / Mohamad Hasnal Jamil ... [et.al] - Mohamad Hasnal, Jamil; Mohd Faris, Mohd Ismail; Muadzan, Hashim; Nik Mohamad Shukry, Ramli (Faculty of Communication and Media Studies, 2003)
For our company logo, we are choosing a sofa as a main object that we put on the center part of our logo. Then, we put the word DARUL AMAN on the top of the logo model by making it curving around the topside. Then the word FURNITURE, we place it under and make it stayed on the sofa to make look more interesting. For all words we are using capital letters. This is because we want to focus it and can catch people eyes on it. For color concept we are using three basic colors it is red, yellow and green. For DARUL AMAN FURNITURE we are using red color because this color we guest is the most suitable color that we can use or interrupt if we want to catch people eyes on it. The sofa are being colored by green color. This is because the green color will help to make the red one look more appear. For the background of the sofa we put an effect from Auto shape. Then put it in yellow color. This is because we would like to make it look more modern and great. All of the color usage as basically inspired form Kedah Darul Aman flag color that contained red, yellow and also green.